Pengaruh Ekstrakulikuler Keagamaan Himpunan Pelajar Masjid At-Taufik (HIPMA) Terhadap Spiritual Quotient (SQ) Siswa - Usep Malik Haerudin; Andini Nurul Barokah; Anidah Inayah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of religious extracurricular activities of the At-Taufiq Mosque Student Association (HIPMA) on the Spiritual Quotient (SQ) of students at SMPN 1 Kadungora. This research uses descriptive regression analysis method. The respondents of this study were all members of the HIPMA religious extracurricular at SMPN 1 Kadungora, totaling 60 people. Based on the results of the study, it shows the influence between the religious extracurricular activities of the At-Taqwa Mosque Student Association (HIPMA) on the spiritual quotient of students at SMPN 1 Kadungora, resulting in a significance value of 0.000 <0.05, meaning that the religious extracurricular activities of the At-Taqwa Mosque Student Association (HIPMA) affect the spiritual quotient of students. Then, the amount of contribution from religious extracurricular activities to the development of students' spiritual quotient based on the coefficient of determination of 0.581 or 58.1% is included in the moderate category, in the interval 0.40 - 0.59. Furthermore, the positive result (+) proves that the linearity value is unidirectional, indicating that if the activeness of students in participating in the religious extracurricular activities of the At-Taqwa Mosque Student Association (HIPMA) is high, then it also encourages the higher spiritual quotient of students.